Effect of Return on Equity (ROE), Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) on Stock Returns - David David; Fenny Krisna Marpaung; Eva Margareth Sarah; Indah Rahmi; Cindy Trinovita Br Perangin Angin (International Journal Of Economics Social And Technology, 2023)
The objective from this research is to test is There is a connection between Returns On equity (ROE), return On Assets (ROA), Debt To Equity Ratio (DER), And Current Ratio (CR) to Stock Returns in the sector BE registered banking for period 4 years, from 2018 to 2021. The method used is descriptive quantitative. From 46 company sector banking in BE, only 26 company Which fulfill the criteria For making sample with technique purposive sampling. On testing hypothesis, study This do analysis linear double by using eviews software application. By testing hypothesis this research, can obtained ROE, ROA, DER And CR in a manner simultaneous Which is variable independent affect Stock Return on the score BE registered banking period 2018-2021. Besides That results testing in a manner partial, ROE No influential significant on Stock Return, ROA has an effect positive and significant to Return Stocks, DER have no effect significant on Stock Returns, and CR has an effect positive and significant on Stock Returns in the sector BE registered banking period 2018-2021.